The fecal carriage rate of extended-spectrum β-lactamase–producing or carbapenem-resistant Enterobacterales among Japanese infants in the community at the 4-month health examination in a rural city - Kawata, Soichiro; Morimoto, Shimpei; Kosai, Kosuke; Kawamoto, Yasuhide; Nakashima, Yumiko; Morinaga, Yoshitomo; Yanagihara, Katsunori; Yoshida, Lay-Myint; Moriuchi, Hiroyuki (Frontiers in Cellular and Infection Microbiology, 2023)
Background Extended-spectrum β-lactamase–producing Enterobacterales (ESBL-E) is a great public health concern globally not only in hospitals but also in the community. To our knowledge, there have been few studies on the prevalence of ESBL-E and much less about carbapenem-resistant Enterobacterales (CRE) among children in the community, and there is no such study in Japan despite such situations. This study aimed to clarify their carriage status among Japanese infants in the community by taking the opportunity of the 4-month health checkup. Methods This prospective analysis was conducted from April 2020 to March 2021 in Shimabara City, Nagasaki Prefecture, Japan. The research-related items were mailed to all subjects with official documents for the checkup. The fecal samples were obtained from the diaper by guardians beforehand and were collected with the questionnaire and then screened for ESBL-E and CRE by a clinical laboratory company with selective agars followed by identification and confirmation. Only the positive samples were analyzed about resistant genotypes. Results One hundred fifty infants aged 4–5 months, over half of the subjects, participated in this study. The overall ESBL-E carriage rate was 19.3% (n = 29), and no CRE carrier was detected among them. All identified ESBL-E were E. coli except for one K. pneumoniae. A significantly higher carriage rate was recorded among the infants born at “Hospital A” (25.0%) than the others (11.3%). Enterobacterales producing CTX-M-9 ± TEM were broadly distributed among the positive samples (65.5%), whereas the CTX-M-1 group was exclusively detected among those from “Hospital A”. Recursive partitioning analysis suggested that delivery facilities might be an important factor for ESBL-E colonization, although the effect could be decreased as they grow. In contrast, no significant effect was observed for other factors such as parent(s) as healthcare worker(s), having a sibling(s), and the mode of delivery. Conclusion This study revealed the ESBL-E and CRE carriage status of Japanese infants in the community for the first time, although the setting is somewhat limited. Our findings indicated that environmental factors, especially delivery facilities, influenced ESBL-E colonization among infants aged 4–5 months, implying the need for strengthening countermeasures against antimicrobial resistance at delivery facilities and communities outside the hospitals.